Assessing Treatment Success or Failure as an Outcome in Randomised Clinical Trials of COPD Exacerbations. A Meta-Epidemiological Study - Alexander G. Mathioudakis; Sachin Ananth; Thomas Bradbury; Balazs Csoma; Pradeesh Sivapalan; Elizabeth Stovold; Gustavo Fernandez-Romero; Zsofia Lazar; Gerard J. Criner; Christine Jenkins; Alberto Papi; Jens-Ulrik Jensen; et al. (Biomedicines, 2021)
A recently published ERS core outcome set recommends that all trials of COPD exacerbation management should assess the treatment success (or “cure” of the exacerbation), defined as a dichotomous measure of the overall outcome of an exacerbation. This methodological systematic review describes and compares the instruments that were used to assess treatment success or failure in 54 such RCTs, published between 2006–2020. Twenty-three RCTs used composite measures consisting of several undesirable outcomes of an exacerbation, together defining an overall unfavourable outcome, to define treatment failure. Thirty-four RCTs used descriptive instruments that used qualitative or semi-quantitative descriptions to define cure, marked improvement, improvement of the exacerbation, or treatment failure. Treatment success and failure rates among patients receiving guidelines-directed treatments at different settings and timepoints are described and could be used to inform power calculations in future trials. Descriptive instruments appeared more sensitive to treatment effects compared to composite instruments. Further methodological studies are needed to optimise the evaluation of treatment success/failure. In the meantime, based on the findings of this systematic review, the ERS core outcome set recommends that cure should be defined as sufficient improvement of the signs and symptoms of the exacerbation such that no additional systemic treatments are required.